Analisis Service Quality pada Aplikasi DANA berdasarkan Sudut Pandang Pelanggan di Daerah Bandung Menggunakan Metode Servqual dan Model Kano - Bob Simon Silalahi; Fergie Joanda Kaunang (TeIKa, 2022)
In the current era of technological advances, all daily activities undergo changes, which were initially manual to digital. Currently, activities are dominated by using mobile applications, for example, in payment transaction systems that are carried out digitally. DANA is one of the most widely used e-wallets by people today. The purpose of this study was to determine the level of customer satisfaction with the quality of service provided by the DANA application and the attributes that have an influence on consumers and the presence or absence of attributes that can change the level of customer satisfaction. The method used is the servqual Method and Kano Model. The Servqual method measures service quality by measuring customer expectations about service quality and their perceptions of the services they receive, then the Kano Model has or no attributes that can change the level of customer satisfaction. the higher the service quality of DANA, the higher the profit and the company lasts longer. This research was conducted in the area of ​​West Bandung with the object of society aged 18-25 years. Based on the results of the analysis using the servqual method, each Servqual indicator has a negative GAP, which means that it is necessary to improve its services by the Fund. The responsiveness dimension has the highest average Gap value of -0.89. While the results of the management using the canoe model there are 10 attributes that affect the level of customer satisfaction. Attributes X6 and X7 are Basic Needs (must have), X8 and X9 affect customer satisfaction based on their desires (O) then the presence of attributes X2, X3, X4, X5, X10 and X11 will increase customer satisfaction, but if there is none it will not lower their satisfaction (A). The Fund should improve its services in this Attractive category because it can increase customer satisfaction significantly. Based on Servqual Method Analysis and Kano Model, Dana needs to improve indicators for customer satisfaction.